GUA TOGI BOGI, HUNIAN BERCIRI MESOLITIK DI NIAS (PERBANDINGAN DENGAN SITUS GUA TOGI NDRAWA) - Ketut Wiradnyana (Berkala Arkeologi Sangkhakala, 2006)
Togi Bogi's one of the caves which located up to the hill around 75 metres from the surface of the sea. There was also an archaeological remains such as artefact and ecofact inside it, that had the same characteristics which was found in Togi Ndrawa’s cave. From the excavation, it’s found mollusk and other lithics that described the culture of the megalithic’s area. The result of the dating analysis using radiocarbon method on the mollusk and cinder indicated the activities at Togi bogi's cave, Nias was about on 4960 ± 130 BP untill 950 ±110 BP